Celebrating health @ 50 in Guyana : a photo gallery 1966-2016 (PAHO/WHO Washington, D.C.US, 2016)
Encompasses the opening of hospitals, clinics, health centres, the launching of strategies, projects, plans and other activities in health.
Keywords: HEALTH